Pendampingan Berbasis Bio-Ecopreneurship untuk Menguatkan Kreativitas dan Minat Berwirausaha Penggiat Majelis Taklim: Bio-Ecopreneurship Assistance to Strengthen Creativity and Entrepreneurial Interest for Majelis Taklim Members - Laelasari, Iseu; Hayya, Adieba Warda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Bio-ecopreneurship’s assistance strengthened creativity and entrepreneurial interests for the members of Majelis Taklim Al-munawwaroh in Bandung Regency. This community development used the Asset-Based Community Development (ABCD) method, with the target subject of assistance being 30 women members of Majelis Taklim, aged 30 to 55 years. Community Development implementers use instruments in the form of observation sheets and deep interviews to photograph the mentoring process and reveal the variety of creativity of participants in making bio-ecopreneurship-based products, such as fermented food and drinks in the form of nata de soya and yoghurt, ecoprint products, used cooking oil soap, and organic liquid fertilizer. The results show that the mentoring activities can stimulate interest, enthusiasm, and curiosity. Based on the monitoring and evaluation results, it can be seen that mentoring activities also have implications for developing the productivity and creativity of the women of the Taklim Council in making new creations such as various varieties of yoghurt flavors, packaging nata de soya, making ecoprint hijabs and tote bags, packaging liquid organic fertilizer and multiple forms of used cooking oil soap. This is the first step in fostering entrepreneurial enthusiasm and capital among the mentoring participants.